Enhancing SMEs as Service Elements: Exploring Community-Centered Management Strategies - Purnamasari, Tia (Golden Ratio of Community Services and Dedication, 2024)
The aim of this research is to investigate the efficacy of community-centered management strategies in enhancing the performance and sustainability of Small and Medium-sized Enterprises (SMEs). Employing a systematic literature review, this study synthesizes insights from diverse perspectives, including stakeholder engagement, collaborative partnerships, and place-based initiatives. The research method involves the analysis of scholarly articles and empirical studies to elucidate the multifaceted nature of community-centered approaches and their implications for SMEs. The findings underscore the significance of stakeholder engagement as a fundamental principle of community-centered management, emphasizing the importance of collaborative partnerships in driving innovation, market access, and brand reputation for SMEs. Moreover, the research highlights the role of social capital in shaping business-community relationships and driving SME outcomes, emphasizing the importance of building trust-based relationships and leveraging relational networks. Additionally, place-based initiatives emerge as catalysts for local economic development and social cohesion, offering SMEs opportunities to create shared value for businesses and communities. Overall, this research contributes to advancing our understanding of community-centered management strategies for SMEs, highlighting their transformative potential in promoting sustainable development and inclusive growth.